Analysis of prolactin receptor expression in the murine brain using a novel prolactin receptor reporter mouse. (23rd August 2018) - Kokay, Ilona C.; Wyatt, Amanda; Phillipps, Hollian R.; Aoki, Mari; Ectors, Fabien; Boehm, Ulrich; Grattan, David R.
Abstract : Prolactin influences a wide range of physiological functions via actions within the central nervous system, as well as in peripheral tissues. A significant limitation in studies investigating these functions is the difficulty in identifying prolactin receptor (Prlr) expression, particularly in the brain. We have developed a novel mouse line using homologous recombination within mouse embryonic stem cells to produce a mouse in which an internal ribosome entry site (IRES) followed by Cre recombinase cDNA is inserted immediately after exon 10 in the Prlr gene, thereby targeting the long isoform of the Prlr. By crossing this Prlr‐IRES‐Cre mouse with a ROSA26‐CAGS‐tauGFP (τGFP) reporter mouse line, and using immunohistochemistry to detect τGFP, we were able to generate a detailed map of the distribution of individual Prlr‐expressing neurones and fibres throughout the brain of adult mice without the need for amplification of the GFP signal. Because the τGFP is targeted to neurotubules, the labelling detected not only cell bodies, but also processes of prolactin‐sensitive neurones. In both males and females, Cre‐dependent τGFP expression was localised, with varying degrees of abundance, in a number of brain regions, including the lateral septal nucleus, bed nucleus of the stria terminalis, preoptic and hypothalamic nuclei, medial habenula, posterodorsal medial amygdala, and brainstem regions such as the periaqueductal grey and parabrachial nucleus. The labelling was highly specific, occurring only in cells where we could also detect Prlr mRNA by in situ hybridisation. Apart from two brain areas, the anteroventral periventricular nucleus and the medial preoptic nucleus, the number and distribution of τGFP‐immunopositive cells was similar in males and females, suggesting that prolactin may have many equivalent functions in both sexes. These mice provide a valuable tool for investigating the neural circuits underlying the actions of prolactin.